The Effects of Transcutaneous Electrical Nerve Stimulation on Post-Episiotomy Pain Severity in Primiparous Women: A Randomized, Controlled, Placebo Clinical Trial: - Shahoei, Roonak; Zakariaee, Seyedeh Soma; Hashemi Nosab, Leila; Moradi, Ghobad; Farshbaf, Mina (Galen Medical Journal, 2019)
Background: Episiotomy or cutting the perineum is the most common operation in obstetrics. Perineal pain is the main complication of episiotomy that affects the quality of life and mental health of the mother. Reducing the pain and side effects of the chemical drugs prescribed for pain relief has attracted the attention of both physicians and scientists. This study was conducted to determine the effects of transcutaneous electrical nerve stimulation (TENS), as an alternative method, on post-episiotomy pain severity. Materials and Methods: This randomized clinical trial was performed on 120 primiparous women who had referred to Sanandaj Besat Hospital in 2018. The patients were divided randomly into three groups, including the intervention group (TENS-On), the placebo group (TENS-Off), and the control group. TENS electrodes were placed near the episiotomy site in genitofemoral and pudendal nerves. The pain was measured after episiotomy in lying, sitting, and activity positions. The pain severity was measured using a pain measurement instrument (numeral rating score) at four-time points, i.e., before the intervention as well as 30, 60, and 120 minutes after the TENS intervention. For data analysis, Pearson correlation, studentâ€™s t-test, Kruskal-Wallis test, ANOVA test, and Mann-Whitney U tests were used. Results: Intragroup evaluation results for placebo and control groups demonstrated no significant difference in the pain score (P>0.05). A significant difference was observed between the mean pain severity of the intervention group and that of the group with walking activities (P=0.04). In terms of the intergroup evaluation, there was a significant difference observed between the mean pain severity of the lying position and that of the control group (P=0.008). Regarding the sitting position, no significant difference was observed between its mean pain severity and that of the other two groups (P=0.04). Conclusion: TENS is an effective and safe method for post-episiotomy pain relief and a routine method used in the obstetrics and gynecology ward. [GMJ.2019;8:e1404]Â 